Effectiveness of Nitrogen Foliar Fertilizer on Rice Productivity on Swampland in Majapahit Village, Lubuk Linggau City - Dora Palupi; Helda Susianti; Limartaida Siahaan; Yus Dwi Yanti; Widya Analisa (Yayasan Sinergi Multidimensi Kreatif, 2025)
Rice is a very important and strategic commodity because it is the main source of carbohydrates for the community. Therefore, an increase in rice production is urgently needed. Swampland is considered a potential option to support food self-sufficiency, given the various advantages it has. One of the main advantages is the availability of abundant water, which is crucial in supporting plant growth, especially in uncertain climatic conditions. Fertilizer is one of the key factors in rice farming. Nitrogen (N) is one of the most important nutrients and should be available to plants. Foliar nutrition can generally increase grain yield while reducing the amount of fertilizer administered through soil application. The purpose of this study is to obtain the concentration and intensity of foliar urea application that is most effective in supporting the growth and yield of rice cultivated in swampland. The experiment was carried out using a complete group random design (RAKL) with a factorial design involving 2 factors and 3 replicates. The first factor is the concentration of urea solution, which consists of 4 levels, namely 3%, 6%, 9%, and 12%. The second factor is the intensity of the application which consists of 3 levels, namely 2 mst, 2 mst, and 4 mst, as well as 2 mst, 4 mst, and 6 mst.